Mobile Ordering Application for a Generic Fast Food Restaurant - Buenaventura, Ricachelle U.; Ignacio, Aris E.; Laspoña, Julian Antonio S. (Future Science / FSH-PH Publications, 2021)
In a restaurant, a customer waiting to be serviced is a phenomenon. Restaurant owners often overlook this matter which sometimes causes the customers to go to a competitor. There are some important factors to be considered a good restaurant such as taste, ambiance, and service. An establishment will attract a substantial number of customers when these factors are managed carefully. Fast service is one of the most important factors in fast food restaurants to avoid losing customers because of considerable delay on the line. During mealtime, customers rush to fast food restaurants to have a quick meal. This research aimed to develop a mobile ordering application for a fast-food restaurant that offers a series of functionalities wherein a customer can order food using this platform. The system was developed using the Agile Methodology in assuring its proper implementation. A survey was performed to establish the acceptability of the mobile application. Five small fast food and restaurant owners were invited to test and answer the survey and another set of fifty prospective customers undergone the same set. As a result, the expected acceptability rating was attained from the survey conducted. Improvements of the system were recommended that were not implemented in the current version due to time constraints and the non-applicability to the current study